3x+9x-4=5+3(2x-7)

Simple and best practice solution for 3x+9x-4=5+3(2x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+9x-4=5+3(2x-7) equation:


Simplifying
3x + 9x + -4 = 5 + 3(2x + -7)

Reorder the terms:
-4 + 3x + 9x = 5 + 3(2x + -7)

Combine like terms: 3x + 9x = 12x
-4 + 12x = 5 + 3(2x + -7)

Reorder the terms:
-4 + 12x = 5 + 3(-7 + 2x)
-4 + 12x = 5 + (-7 * 3 + 2x * 3)
-4 + 12x = 5 + (-21 + 6x)

Combine like terms: 5 + -21 = -16
-4 + 12x = -16 + 6x

Solving
-4 + 12x = -16 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-4 + 12x + -6x = -16 + 6x + -6x

Combine like terms: 12x + -6x = 6x
-4 + 6x = -16 + 6x + -6x

Combine like terms: 6x + -6x = 0
-4 + 6x = -16 + 0
-4 + 6x = -16

Add '4' to each side of the equation.
-4 + 4 + 6x = -16 + 4

Combine like terms: -4 + 4 = 0
0 + 6x = -16 + 4
6x = -16 + 4

Combine like terms: -16 + 4 = -12
6x = -12

Divide each side by '6'.
x = -2

Simplifying
x = -2

See similar equations:

| 4x+32=128 | | 13-(-2x-5)=8 | | mx+ny=46 | | 7x-18=5x+2 | | 5=v+6 | | F(x)=(2x+5)(x-1) | | .15(x-4)=9.9-.3(x-1) | | dy/dx=x^6y^-5 | | 94=-2x-6+12 | | 6(2x-1)x-12=3(7x+6) | | (x+4)(5x-4)=o | | 625^(3/4) | | 32^(1/5) | | -4(y+6)=-4y-23 | | 4(x-5)-3x/4=2/5 | | -4.2v+6.1=2.1v+4 | | 7x-40y=-146 | | 7(4m+8)=-32+6m | | -6u-5=2u-13 | | -4z+18=3(2z-4) | | x^3-36x^2+432x-1735=0 | | 2(1+6p)=13+p | | -7w-17=1 | | 7x-(4)+9x-(40)=180 | | -w-13=3w-1 | | 9=-2t-3 | | -2y+4=0 | | 2(3x+4)=7x+2-5x | | -7-7r=7(5-2r) | | (7-9i)+(7+3i)= | | -4/5=3y | | 1/10-r/6=-3/10 |

Equations solver categories